Demand, mobility, and constraints: Exploring travel behaviors and mode choices of older adults using a facility-based framework. (June 2022) - Zhou, Yang; Yuan, Quan; Ding, Fangyi; Chen, Mingyang; Yang, Chao; Guo, Tangyi
Abstract: The steady trend of aging has caused great concern on how cities should better accommodate the social needs of aged population. Older people in general have more leisure time than younger adults but are found highly constrained in daily travel. To examine the imbalance between travel demand and transport supply among older adults, this paper decomposes their daily travel into two categories (visits to non-ubiquitous and ubiquitous facilities) according to major characteristics of travel behaviors using Nanjing Household Travel Survey data. Multinominal logit (MNL) models are applied to exploit the effects of household and personal characteristics, trip characteristics, local supplies, and public transport services on travel mode choices. Results show that (i) travel demand and transport supply are highly unbalanced for most non-ubiquitous facilities, (ii) relative to younger adults, older adults travel further and highly rely on public transport to access non-ubiquitous facilities, (iii) providing more public transit services nearby non-ubiquitous facilities are more reliable to increase the accessibility of older adults than increasing the number of facilities. These results would help policy-makers better understand travel behaviors of older adults and develop strategies to accommodate their travel demand, especially from the perspective of facility network reorganization. Highlights: Older adults are strongly constrained in travels to non-ubiquitous facilities. Older adults highly rely on public transports due to physical issues and limited car usage. Spatial mismatch of demand and opportunities among non-ubiquitous facilities is significant. Improving transit services nearby non-ubiquitous facilities can help address the mismatch.